1953
DOI: 10.1177/1.6.493
|View full text |Cite
|
Sign up to set email alerts
|

The Histochemical Detection of Zinc

Abstract: The presence of zinc in small coimcemmtrations in most plant and animal tissues has i)een demoimstrated in numerous iimstances, but its physiological function is * This investigation was supported in part h)y a research grant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
1

Year Published

1956
1956
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(16 citation statements)
references
References 9 publications
0
14
1
1
Order By: Relevance
“…Dithizone Staining-Zn 2ϩ bound to protein immobilized on a PVDF membrane was following renaturation detected with dithizone (0.5 mg/ml) as described (44).…”
Section: Casknekgkevvaksmentioning
confidence: 99%
“…Dithizone Staining-Zn 2ϩ bound to protein immobilized on a PVDF membrane was following renaturation detected with dithizone (0.5 mg/ml) as described (44).…”
Section: Casknekgkevvaksmentioning
confidence: 99%
“…They also described a rise in leukocyte zinc towards normal when subjects with chronic granulocytic leukemia responded to therapy. We have reported on the decreased amount of zinc in leukocytes of patients with hepatic cirrhosis (9), and high zinc levels in eosinophils have been described (10,11).…”
mentioning
confidence: 99%
“…They found great variations in concentration of the metal, as much as 18-fold, for different portions of the gland. On the other hand, Mager, McNary and Lionetti (1953), using histochemical methods, could not detect differences in zinc content between the anterior and posterior lobes of the human, canine and simian prostates. In the rat, Gunn et al (1955) found that the dorsolateral prostate concentrates about 20 times as much 65Zn as the ventral portion.…”
Section: Discussionmentioning
confidence: 72%
“…The localization of 65Zn by the border epithelium is in accord with the radioautograph published by Daniel et al (1956) for human prostate and with those presented by Wetterdal (1958) and Millar, Vincenlt and Mawson (1961) for the dorsolateral prostate of the rat. Using the dithizone stain, Mager et al (1953) studied the prostates of the dog, man, monkey and rabbit, reporting that the apical portions of the secretory cells were most intensely stained. They found that the associated connective and muscle tissues did not contain zinc.…”
Section: Discussionmentioning
confidence: 99%